Impact of Magnetic Field on Peristaltic Transport of Nano-Coupled Stress Fluid in an Inclined Porous Tube - Molimol , M.P.; Prasad, Karanamu Maruthi; Subadra, Nemani (East European Journal of Physics, 2025)
This study provides a theoretical investigation of peristaltic transport of couple-stress nanofluid under the influence of a magnetic field in an inclined porous tube. With low Reynolds number, long wavelength approximations, appropriate analytical methods are employed to investigate the fluid’s velocity, frictional force, time-averaged flux, nanoparticle phenomena, pressure drop, and temperature profile. The effects of various physical parameters, including the thermophoresis parameter, Brownian motion parameter, local nanoparticle Grashof number, and local temperature Grashof number, on frictional force and pressure drop characteristics are investigated. Graphs are used to illustrate expressions for pressure drop, velocity, nanoparticle phenomena, temperature profile, and frictional force.